Influence of Climate and Duration of Stream Water Presence on Rates of Litter Decomposition and Nutrient Dynamics in Temporary Streams and Surrounding Environments of Southwestern USA - Lohse, Kathleen A.; Gallo, Erika L.; Meixner, Thomas (Frontiers in Water, 2020)
Ephemeral and intermittent streams are increasing with climate and land use changes, and alteration in stream water presence or flow duration will likely affect litter decomposition and nutrient dynamics in channel and riparian zones more than uplands. To investigate the influence of varying climate and stream flow regimes on rates of decomposition and associated nutrient dynamics, we used a space-for-time substitution design in which we deployed a common leaf litter across a range of ephemeral to seasonally- intermittent stream reaches (10) and landscape positions (channel, riparian, upland) in Arizona, USA over an 18-month period. We also measured soil physio-chemical properties and nutrient dynamics associated with these reaches and positions. Consistent with expectations, rates of litter decomposition (k) decreased significantly in the channels as cumulative percentage (%) of water presence decreased below 40%. Indeed, differences in cumulative duration of water presence as well as channel bed material silt content explained 80% of the variation in k across flow regimes. In contrast, decay rates of the common litter across sites were surprisingly similar in upland and riparian positions despite large differences in climate, specifically precipitation (160-516 mm). Relatively similar litter nitrogen immobilization and soil moisture in upland and riparian environments helped to explain the lack of difference in k and soil nutrient dynamics in these environments. Collectively, our findings indicate that stream water presence may be a more important indicator of ephemeral and intermittent stream function than stream flow alone and that riparian zones in these dryland regions may be less responsive to changes in climate and associated subsidies of stream flow.